Letter : Re clothing for Spain - Conley, Andrew
028-0109-001 TELEGRAMS: AMALGAMATE, LEEDS. TELEPHONE: LEEDS 20557. NATIONAL UNION OF TAILORS & GARMENT WORKERS. Incorporating the Amalgamated Society of Tailors & Tailoresses, Scottish Operative Tailors & Tailoresses and the Garment Workers Union. General President: G. Rowlerson. General Secretary: A. Conley. HEAD OFFICE: Union Chambers, 20 Park Place, LEEDS, 1. 11th January 1937. 9/1/962. Mr. H. V. Tewson, Trades Union Congress General Council, Transport House, (South Block), Smith Square, LONDON, S.W.1. Dear Mr. Tewson, RE Clothing for Spain. Following upon our conversation just before Christmas, I met a number of representatives of our Leeds Branch during the Christmas holiday, and after explaining the project I had in mind, encountered unexpected opposition. However, I think this can be overcome. I am asking some members of my Executive to meet me at the week-end, and will again write you immediately afterwards. With best wishes. Yours sincerely, A. Conley, General Secretary. 292/946/28/109